المعجمية العربية و ترجمة المصطلح اللساني - كبير, الشيخ (جامعة الوادي - University of Eloued, 2021)
الملخص : يزخر تراثنا العربي بعديد من المعجمات التي تعبر بحق عن إجتهادات علمية لا يستهان بها، فهي زاد الباحث في اللغة و الأدب وغيرهما. كما عرفت المعاجم العامة و المتخصصة في العصر الحديث قفزة نوعية و على رأسها اللّسانيات، حيث لعبت الترجمة دورا جوهريا رغم ما يشوبها من إختلال و فوضى، الأمر الذي قلّل من علميّة و دقة المصطلحات المترجمة. و من هنا جاءت هذه الورقة البحثية لمعالجة المعجم اللساني في ضوء المعجمية العربية الحديثة و تعددية الترجمة. The Arabic heritage is rich in many lexicons that truly express scientific efforts and cannot be underestimated, as it is the researcher’s supplement in language and literature. The linguistics has been on top of the general and specialized lexicons which have also known quantum leap in the modern era. Furthermore, translation has played a fundamental role despite its imbalance and chaos that has reduced the scientific and accuracy of Arabic linguistics. Hence, this research paper aims to treat the linguistic lexicon in light of modern Arabic lexicography and the plurality of translation .
مقال
Keywords: المعجمية، العربية، ، الترجمة، المصطلح ، اللسانيات; Lexical, Arabic, translation, term, linguistics